Analisis Sistem Informasi Akuntansi Pada Penerimaan, Pengeluaran & Transparansi Kas di Kantor Kelurahan Banjar Serasan - Andi Farhan; Muhammad Emir YA; Wukuf Dilvan R (Magister Ilmu Akuntansi Universitas Jambi, 2023)
The purpose of this study was to understand the implementation of the Accounting Information System on Cash Receipts, Disbursements, and Transparency in the Banjar Serasan Village Office. This study uses a qualitative approach to gain a comprehensive understanding. The research data consists of primary data obtained through interviews with informants involved in the financial management process, as well as secondary data obtained through observation and documentation studies. Data collection techniques used include interviews, observation, and documentation studies. The analytical method used in this study adopts a postpositivism philosophy, which focuses on objective understanding and objective data analysis. The data collected was analyzed thematically, identified emerging patterns and themes, and given an in-depth interpretation. The results showed that the accounting information system implemented in the Banjar Serasan Village Office made a significant contribution to the mechanism of cash receipts and disbursements. However, research also finds that transparency to the public is limited due to local regulations that prohibit public disclosure of financial information. Informants in this study revealed that these limitations are the result of policies that have been set and must be followed.